From Necropraxis to Necroresistance: Transgender Experiences in Latin America - Rodríguez Madera, Sheilla L. (Journal of interpersonal violence, 2022)
Latin America is one of the deadliest regions for trans communities. Scientific research generated in the region has reported that trans people live through a complicated panorama shaped by multiple forms of oppression, extreme violence, and micro-aggressions. Although necropolitics, as a theoretical approach, has been useful to understand how State policies negatively affect trans individuals, it does not fully account for informal dynamics within groups and among individuals that are potentially lethal for this population in Latin America. To account for this gap, the author proposes two novel concepts: necropraxis (a pattern that manifest itself in everyday social interactions, through which gradual small doses of death are delivered to eliminate, symbolically and/or literally, trans people); and necroresistance (the ways in which trans people defy the threats imposed by necropraxis through ?ordinary? acts manifested in their everyday life). The main objective of this article is to put forth definitions for these two concepts and identify how they apply in the context of trans communities in three countries of the region: Guatemala, Argentina, and Chile. To achieve the latter, the author relies on her ethnographic work in these contexts. Data were gathered through parcipant observation, in-depth interviews with trans persons (N = 11) and informal conversations with individuals during the site visits. A deductive qualitative analysis was conducted. Results evidence how the manifestation of necropraxis and necroresistance were highly influenced by the historical, political, economic and sociocultural context of each country. This study provides valuable information to help both policymakers and other stakeholders understand the problem?s magnitude in the region and the ways necropraxis is experienced in everyday relations between trans individuals and others. Similarly, through the understanding of what constitutes necroresistance and its value, the proposed framework could help them outline prevention and management strategies to strengthen trans communities in different countries.